Differential Item Functioning of the Boston Naming Test in Cognitively Normal African American and Caucasian Older Adults - Pedraza, Otto (2009)
Scores on the Boston Naming Test (BNT) are frequently lower for African American when compared to Caucasian adults. Although demographically-based norms can mitigate the impact of this discrepancy on the likelihood of erroneous diagnostic impressions, a growing consensus suggests that group norms do not sufficiently address or advance our understanding of the underlying psychometric and sociocultural factors that lead to between-group score discrepancies. Using item response theory and methods to detect differential item functioning (DIF), the current investigation moves beyond comparisons of the summed total score to examine whether the conditional probability of responding correctly to individual BNT items differs between African American and Caucasian adults. Participants included 670 adults age 52 and older who took part in Mayo's Older Americans and Older African Americans Normative Studies. Under a 2-parameter logistic IRT framework and after correction for the false discovery rate, 12 items where shown to demonstrate DIF. Six of these 12 items (“dominoes,” “escalator,” “muzzle,” “latch,” “tripod,” and “palette”) were also identified in additional analyses using hierarchical logistic regression models and represent the strongest evidence for race/ethnicity-based DIF. These findings afford a finer characterization of the psychometric properties of the BNT and expand our understanding of between-group performance.